PENGARUH PEMBERIAN PUPUK ORGANIK CAIR (POC) TOP G2 DENGAN DOSIS YANG BERBEDA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAYAM HIJAU (Amaranthus tricolor L.) - Aldi Poenamo; MaYa F. Roman; Nardi Matias Leo; Nur Aini Bunyani (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
Liquid organic fertilizer (LOF) is a fertilizer produced through the fermentation of organic materials that contains complete nutrients and is easily absorbed by plants. The use of LOF offers a solution to reduce dependency on chemical fertilizers, which have negative impacts on soil fertility. This study was motivated by the need for environmentally friendly fertilization technology to improve the growth and yield of green amaranth (Amaranthus tricolor L.). The research was conducted from March to May 2025. The objective of this study was to determine the effect of applying TOP G2 LOF at different doses on the growth and yield of green amaranth, as well as to identify the most effective dosage. The method used was a Completely Randomized Design (CRD) with four treatments: P0 (control), P1 (5 ml/L), P2 (10 ml/L), and P3 (15 ml/L), each replicated three times. The observed parameters included plant height and number of leaves. Data were analyzed using analysis of variance (ANOVA) and the Least Significant Difference (LSD) test at the 5% significance level. The results showed that the application of TOP G2 LOF had a significant effect on the number of leaves and plant height. The P3 treatment (15 ml/L) produced the best results with an average plant height of 97.33 cm and an average of 23.67 leaves. Thus, the 15 ml/L dosage of TOP G2 LOF was effective in enhancing plant growth.